An Assessment of Paths for Transforming IFC to Shapefile for Integration of BIM and GIS - Zhu, J.; Wang, P.; Wang, Xiangyu (2018)
© 2018 IEEE. Building Information Modelling (BIM) could provide detailed 3D building models to Geographic Information Systems (GISs) for the emerging studies in smart cities/digital cities. During information exchange, Industry Foundation Classes (IFC) containing rich building information is the most used data format in BIM. However, GIS does not the capacity to directly consume the data in IFC due to data incompatibility between the two systems. Consequently, IFC files have to be transformed into a format that is accessible to GIS. Shapefile is one of them, given its popularity in geospatial science. This study tests the different formats and methods for transforming IFC to shapefile, assesses their performance, in order to offer a ranking, from which better decisions could be made when choosing an appropriate intermediate data format. The results show direct transformation from IFC to shapefile retained the most geometry and semantic information. If the direct transformation method does not work in some cases, 3DS, VRML, or SKP could be used as alternatives to retain most of the information, while DWG, DXF, KML, and KMZ should not be considered due to their poor performance in the test.